Analisis Soal Lomba Cerdas Cermat Tingkat Mahasiswa Tadris Matematika - Hidayu Sulisti; Sarassanti, Yumi (Jurnal Padegogik, 2025)
This study aims to evaluate the quality of quiz questions for student-level students, organized by the Mathematics Education Study Program, FTIK IAIN Pontianak together with the Mathematics Education Student Association. The evaluation was carried out based on aspects of material, construction, language, and Bloom's Taxonomy. The mathematics materials presented in the competition include Algebra, Geometry, Number Theory, Trigonometry. Data were taken from documents of questions, answers, and participant scores. The analysis showed that the majority of questions were of good quality, although some aspects, such as the balance of cognitive levels in Bloom's Taxonomy, needed improvement. This study is expected to be the basis for the development of similar competitions in the future